PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, ARUS KAS OPERASI DAN CAPITAL INTENSITY TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI)TAHUN 2019-2021 - Agustria, Serly; Sembiring, Seniwati; Safriandi, Ferry (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2024)
This study aims to ascertain the impact of operating cash flow, Capital intensity, profitability, and company size on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (BEI) between 2019 and 2021. The population used in this study consisted of 213 individuals, and 42 samples were collected over the course of three years, yielding 126 observation data points. The purposive sampling technique was followed when applying the collected samples. Logistic regression analysis is the data analysis method that is applied. Based on the research findings, it can be concluded that while operating cash flow and Capital intensity do not have an impact on financial distress, company size and profitability do. Subsequently, Financial distress is influenced concurrently by operating cash flow, Capital intensity, profitability, and company size.